Anthropometric criteria in the diagnosis of malnutrition in child-assistance programs - Monteiro, Carlos Augusto (Revista de Saúde Pública, 1984)
Through the examination of the theory which supports the evaluation of nutritional status by mean of anthropometry, and after consideration of characteristics and objectives of children's primary health care, guidelines for the anthropometric-nutritional diagnosis carried out at health centre level are suggested. Further, after consideration of the physiology of growth as well as of evidence on the epidemiology of malnutrition in Brazil, specific criteria for the diagnosis of malnutrition and the needs of nutritional rehabilitation are proposed, with a view to the assessment of the efficacy of treatment and the determination of cure.